2011
DOI: 10.1590/s1806-66902011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência no uso de nitrogênio e correlação fenotípica em populações tropicais de milho no Tocantins

Abstract: Resumo -O objetivo deste trabalho foi avaliar a eficiência no uso do nitrogênio e a correlação fenotípica de 24 populações de milho no Sul do Tocantins. Foram realizados dois experimentos, cada um correspondendo a um nível de adubação nitrogenada (alta e baixa) plantados no dia 21/11/2009. Os tratamentos foram constituídos de 24 populações obtidas do Programa de Melhoramento de Milho da Universidade Federal do Tocantins e uma variedade comercial, BR 106, usada como testemunha. O delineamento experimental utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
4
8
0
11
Order By: Relevance
“…For the densities of 60,000 and 80,000 plants ha -1 there was increase in 1000 grain weight with increasing rates of N. The density of 60,000 plants ha -1 had higher 1000 grain weight in both spacings, 0.45 and 0.90 m. This response indicates a greater effect of competition among plants in density of 80,000 plants ha -1 (Figure 2f). The variable 1000 grain weight increased linearly with N rates in both spacings, which was consistent with the results of Amaral Filho et al (2005) and Cancellier et al (2011) who found direct correlation (0.52) between the 1000 grain weight and yield, increasing yield with increasing N rates.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For the densities of 60,000 and 80,000 plants ha -1 there was increase in 1000 grain weight with increasing rates of N. The density of 60,000 plants ha -1 had higher 1000 grain weight in both spacings, 0.45 and 0.90 m. This response indicates a greater effect of competition among plants in density of 80,000 plants ha -1 (Figure 2f). The variable 1000 grain weight increased linearly with N rates in both spacings, which was consistent with the results of Amaral Filho et al (2005) and Cancellier et al (2011) who found direct correlation (0.52) between the 1000 grain weight and yield, increasing yield with increasing N rates.…”
Section: Resultssupporting
confidence: 90%
“…Nitrogen fertilization should consider the expected grain yield and soil organic matter content (Argenta, 2001), since nitrogen interferes positively on yield (Cancellier et al, 2011;Farinelli & Lemos, 2012) when other factors are not limiting. In southern Brazil (Ceretta, 2000) and in and in the whole country (Coelho, 2007), corn yield is limited by insufficient N fertilization to the extent that the increase in yield with increasing nitrogen rates is represented by the increase in the number and weight of grains and spike length (Kappes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Isto se deve, dentre outros fatores, à presença de altas temperaturas, aliada ao baixo nível tecnológico empregado pelos produtores e à escassez de sementes melhoradas de variedades adaptadas às condições de estresses abióticos, tais como as variações climáticas e nutricionais; neste último caso, relacionado ao N, fósforo (P) e potássio (K), dentre outros (Cancellier et al, 2011;Souza, 2007).…”
Section: Introductionunclassified
“…Além disso, promove alterações no peso de cem sementes e peso hectolitro (Cancellier et al, 2011), e pouca (Welch, 1969) ou nenhuma alteração significativa no teor de óleo dos grãos (Duarte et al, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation